Highway Art Policy Revisited: Rethinking Transfers of Copyright Ownership in State-Owned Transportation Artwork - Horn, Rachel (The Columbia Journal of Law & the Arts, 2020)
In 2016, the California Department of Transportation ("Caltrans") revised its policy standards with respect to the intellectual property rights of artists who create works of public art installed within the state highway system. While Caltrans had previously allowed artists to keep their copyrights subject to a nonexclusive license of certain reproduction rights to the state, the 2016 policy (the “Transportation Art Policy”) requires artists to assign their “entire rights, title and interest in” such works of art to Caltrans, including their “common law and federal copyright ownership rights.” The artist must execute a copyright assignment and transfer agreement, which Caltrans must approve, before the art is installed. This requirement exists even though the policy assumes that certain local “public agencies,” not the state of California itself, will be responsible for commissioning works of art; the policy directs the commissioning agency for a given work of art to also sign onto the assignment and transfer agreement. This Note argues that state policies that, like Caltrans’, require a transfer of copyright in works of public art are ill-fitted to their purposes, and that the goals of copyright law are better served by alternative contractual arrangements. In Part I, I provide an overview of the legal landscape in the United States with respect to transfers of copyright ownership, visual artists’ moral rights, and public art commissions. In Part II, I outline the substance of Caltrans’ Transportation Art Policy and the possible justifications for its 2016 revision, and then show why the policy is both a poor fit for those presumptive objectives and an unwarranted burden on stakeholders. Finally, in Part III, I discuss alternatives to public art policies that require copyright transfer. I argue that states or state agencies seeking to own public artwork should, as Caltrans once did, allow artists to retain copyright provided that they grant the state a nonexclusive license for reasonable public uses. The advantage of such an approach—which many other states already employ—is that it offers reasonable protection for the state’s legitimate interests in avoiding liability and enforcing the copyright, without the attendant harms to artistic creativity and to the public.